Temperature and water level measurement of liquid in a tank using fiber Bragg Grating - Ameen, O. F. (Penerbit UTM Press, 2016)
In this work, measurement of temperature and liquid level were performed simultaneously using fiber Bragg grating (FBG) sensors. A multi-channel Fibre Interrogator with built-in ASE laser source operating around 1552 to 1568 nm was employed to record a shift in Bragg wavelength due to contribution from both temperature and hydrostatic pressure of liquid weight in the tank. Results show a linear response between liquid level and temperature readings against the shift in Bragg wavelength for liquid level up to 85 cm in height and the temperature range of 27 to 77 ºC. The sensitivity of the sensor head for water level measurement is 10.57 pmcm-1, while the sensitivity for temperature measurement is 11.28 pm/ºC respectively.